2006
DOI: 10.1038/sj.bmt.1705246
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic platelet transfusion strategy is safe and feasible in patients after autologous peripheral blood stem cell transplantation

Abstract: Prophylactic platelet transfusions are considered as standard in most hematology centers, but there is a long-standing controversy as to whether standard prophylactic platelet transfusions are necessary or whether this strategy could be replaced by a therapeutic transfusion strategy. In 106 consecutive cases of patients receiving 140 autologous peripheral blood stem cell transplantations, we used a therapeutic platelet transfusion protocol when patients were in a clinically stable condition. Platelet transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 20 publications
2
62
1
4
Order By: Relevance
“…The latter strategy has been documented to be safe in a select group of patients: those undergoing autologous peripheral blood stem cell transplantations. 20 In this study, the need for plt transfusions was reduced by as much as 50% when transfusions were given only for active bleeding.…”
Section: Indications For Plt Transfusionsmentioning
confidence: 89%
“…The latter strategy has been documented to be safe in a select group of patients: those undergoing autologous peripheral blood stem cell transplantations. 20 In this study, the need for plt transfusions was reduced by as much as 50% when transfusions were given only for active bleeding.…”
Section: Indications For Plt Transfusionsmentioning
confidence: 89%
“…13,14 Recently, use of therapeutic vs prophylactic transfusion has been espoused, but some TBIcontaining regimens required more transfusions because of mucositis when transfusions were utilized only for symptoms or bleeding. 15 Other groups have also found faster engraftment but more gastrointestinal bleeding with this approach. 16 Previous retrospective studies have shown that CD34 þ cell counts in the graft, platelet counts at start of conditioning, local radiation and fever all influence time to platelet recovery.…”
Section: Discussionmentioning
confidence: 99%
“…17 Thus, the overall benefit of a prophylactic platelet transfusion policy over a policy to use platelets only therapeutically is not well established. It is important to note that there are now some data, albeit observational, to suggest that a treatmentbased platelet transfusion strategy may indeed be safe and effective in clinical practice.…”
Section: Prophylactic Platelet Transfusionsmentioning
confidence: 99%
“…This is exemplified by the results of a recent study of therapeutic platelet transfusions in hematopoietic stem cell autograft patients in Germany. 17 It is also possible that patient selection may be the key to the safety of therapeutic only-based platelet transfusion.…”
Section: Prophylactic Platelet Transfusionsmentioning
confidence: 99%